Cancer incidence and mortality from exposure to radon progeny among Ontario uranium miners. Issue 12 (20th September 2016) - Navaranjan, Garthika; Berriault, Colin; Do, Minh; Villeneuve, Paul J; Demers, Paul A
Abstract : Objectives: The study objectives were to extend the follow-up of the Ontario uranium miners cohort, one of the largest cohorts of uranium miners with low cumulative exposures, to examine the relationship between radon exposure and lung cancer mortality and, for the first time incidence, and address gaps in the literature, including dose–response relationship between radon exposure and other cancer sites, and non-cancer mortality. Methods: The cohort of mine and mill workers was created using data from Canada's National Dose Registry and the Ontario Mining Master File. The follow-up for the cohort was recently extended for mortality (1954–2007) and for the first time includes cancer incidence (1969–2005). The Poisson regression was used to estimate relative risks (RR) and excess relative risks (ERR) and their 95% CIs with levels of cumulative radon exposure. Results: The cohort consisted of 28 546 male miners with a mean cumulative radon exposure of 21.0 working level months (WLM). An increased risk of lung cancer and a dose–response relationship was observed with cumulative radon exposure. Miners exposed to >100 WLM demonstrated a twofold increase in the risk of lung cancer incidence (RR=1.89, CI 1.43 to 2.50) compared with the non-exposed group, and a linear ERR of 0.64/100 WLM (CI 0.43 to 0.85), with similar results observed for mortality. No association was observed for other cancer sites (stomach, leukaemia, kidney and extrathoracic airways) or non-cancer sites (cardiovascular diseases) with increasing cumulative exposure to radon. Conclusions: These findings suggest no increased risk of cancer sites other than lung or non-cancer mortality from relatively low cumulative exposure to radon.